2014
DOI: 10.7771/2157-9288.1069
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Quality K-12 Engineering Education: Research and Development

Abstract: for additional information. This is an Open Access journal. This means that it uses a funding model that does not charge readers or their institutions for access. Readers may freely read, download, copy, distribute, print, search, or link to the full texts of articles. This journal is covered under the CC BY-NC-ND license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
232
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(244 citation statements)
references
References 12 publications
3
232
0
9
Order By: Relevance
“…To accomplish this, the instances coded as EBR were mapped to the Framework for Implementing Quality K-12 Engineering Education 31 , which defines the characteristics of K-12 engineering. This framework identifies nine key indicators that define engineering in K-12.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, the instances coded as EBR were mapped to the Framework for Implementing Quality K-12 Engineering Education 31 , which defines the characteristics of K-12 engineering. This framework identifies nine key indicators that define engineering in K-12.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these essential aspects of pre-college engineering education only scratch the surface of what is Page 26.1014.2 necessary to produce the quantity and quality of engineers, and citizens, for which we aspire to as a nation. Because of the ability of engineering to develop technical literacy and critical thinking skills, amongst other attributes, engineering education in the K-12 setting has a greater potential to enrich our citizenry than just expanding the pipeline to the engineering career pathway 5,6 . Therefore, we agree with Cunningham & Lachapelle 7 in the following statement:…”
Section: Frameworkmentioning
confidence: 99%
“…Thus, K-12 educators can use the implementation of engineering instruction to develop what are normally deemed "soft" skills in their students. Ethics, teamwork, and communication are essential for a sufficient K-12 engineering education 5 .…”
Section: Frameworkmentioning
confidence: 99%
“…Marshall andBerland (2012) posited that the primary goal of any pre-collegiate engineering programs should be to develop a command of the engineering design process that transcends traditional mathematics and science curriculum goals. In a more multi-dimensional study, Moore, et al (2014) proposed a framework and identified twelve key indicators for describing and designing effective K-12 engineering programs. These indicators include (a) applying concepts in science, engineering, and mathematics and (b) conceptualizing the engineering profession.…”
Section: Introductionmentioning
confidence: 99%
“…In a more multi-dimensional study, Moore, et al (2014) proposed a framework and identified twelve key indicators for describing and designing effective K-12 engineering programs. These indicators include (a) applying concepts in science, engineering, and mathematics and (b) conceptualizing the engineering profession.…”
Section: Introductionmentioning
confidence: 99%